Вимога щодо несумісності як складовий елемент конституційно-правового статусу суддів - Кравчук, В.; Kravchuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Статтю присвячено аналізу вітчизняного та зарубіжного конституційного законодавства про судоустрій і статус суддів в частині вимог щодо несумісності суддівської роботи з іншими видами діяльності. Вимога щодо несумісності посади судді зі здійсненням іншої діяльності зумовлена публічно-правовими інтересами забезпечення розподілу державно-владних повноважень між посадовими особами органів законодавчої, виконавчої та судової влади. Розглянуто вимогу щодо несумісності суддівської роботи як один з елементів конституційно-правового статусу суддів. The article deals with the analysis of the national and foreign constitutional laws on the judicial system and the status of judges in terms of the requirements regarding the incompatibility of judge's work with other types of his activities. The requirement of incompatibility of the position of a judge with the other activities is conditioned by the public-legal interests of ensuring the distribution of powers of the government between the officials of legislative, executive and judicial branches. The requirement for the incompatibility of judicial work is considered as one of the elements of the constitutional and legal status of judges, and which is an additional (non-core) structural element of their legal status since it determines the scope of their rights and responsibilities. The key findings of the study argue that the requirement of incompatibility of the position of judges with other types of their activities is conditioned by the need to guarantee impartial objective and timely justice for individuals and legal entities.
Requirement of Incompatibility as an Integral Part of the Constitutional and Legal Status of Judges
Keywords: вимога щодо несумісності; конституційно-правовий статус суддів; правовий статус суддів; суд; суддя; incompatibility requirement; constitutional and legal status of judges; legal status of judges; court; judge